Psychological Theories in Science Education: Bridging the Gap Between Theory and Practice - Dodi Setiawan Riatmaja; Natalia Holub; Ibrahim Haroun (International Journal of Educational Narratives, 2024)
The integration of psychological theories into science education has gained increasing attention as educators strive to improve student learning outcomes. Despite the wealth of psychological frameworks available, there remains a significant gap between theory and practice in the context of science teaching. Psychological theories, such as cognitive load theory, constructivism, and socio-cultural learning, offer valuable insights into how students learn and engage with scientific concepts. However, their application in real classroom settings is often underexplored. This research aims to investigate how psychological theories can be effectively integrated into science education practices and explore the challenges educators face when attempting to bridge the gap between theoretical knowledge and practical teaching methods. The study employs a mixed-methods approach, combining quantitative surveys with qualitative interviews to gather data from science educators across various educational levels. The findings indicate that while educators are generally familiar with psychological theories, there is a lack of consistent implementation in the classroom. Teachers report difficulties in adapting these theories to diverse student needs and varying classroom environments. The study concludes that greater professional development and practical resources are essential to help educators apply psychological theories effectively in science education. In conclusion, bridging the gap between psychological theories and science education practice requires a concerted effort from both educators and policymakers. Training programs should focus on equipping teachers with the knowledge and tools needed to integrate psychological principles into their teaching methods, ensuring more effective science instruction.